Building People to Build Business Case Study: Role of Perwira Affin Bank's School of Banking - Lim, Lian Chiaw (1999)
The aim of training is to improve job performance by increasing knowledge, developing skills and modifying attitudes so that individuals can work in the most economical, efficient and satisfying way. Training and development has became crucial with the rapid advances in technology and became one of the most vital elements in Human Resource Development process. The purpose of this study is to know how Perwira Affin Bank's School of Banking in playing their roles as training and development centres to achieve the Banks' objective and commitment towards building its people to build its business. This study also to analyst the effectiveness of School of Banking in human resource and development. This study is based on the relationship between the Bank's objectives, School of Banking structure, conduct, and performance approach. The structure will affect the conduct and subsequently affect the performance of the school. Descriptive method is used to determine factors and problems that influence the effectiveness, strength and weaknesses of the school. The systematic training approach through the Training and HRD process model used as determinants. This study found that the Bank shown high commitment towards it human resource development that proven they are committed to building people to build business. The School of Banking has been playing its roles as human resource training and development centres. In order to be more effective and efficient as preferred learning centre, Training and HRD process model is a useful model that the Banks should consider to improve it training school performance. This would contribute directly towards the building of capable and competent workforce. Its has potential of being developed into a strategic advantage to meet an ever increasing challenges in the future.